The Impact of Electronic Banking Services on the Profitability of Commercial Banks:An Applied Study on Jordanian Commercial Banks - Alzoubi, Saddam; Alafeef, Mohammad (The Arab Journal of Administration, 2023)
The current study aimed to demonstrate the impact of electronic banking services on the profitability of commercial banks “from the perspective of employees. The study population consisted of (13879) employees and administrators in six major banks in Jordan. To achieve the objectives of this study, a simple random sample was taken by relying on determining the size of the sample. drawn on the size of the total community, and the sample size was (351), administrators and employees from Jordanian commercial banks that provide banking services for the year 2021 -2022 , the predictive descriptive approach was used to suit the study, and to achieve the objectives of the study, the researcher developed a questionnaire to measure the impact of electronic banking services on the profitability of commercial banks from the perspective of employees , and its psychometric characteristics were verified .The study tool (questionnaire) was distributed to the sample . All questionnaires were retrieved, as they were all valid for coding and analysis, which constituted the actual sample. The results indicated that the values of the arithmetic mean, standard deviations, and the degree of Estimation of the responses of individuals on the items of electronic banking services as a whole came with a (high) degree, and the results indicated that there is a strong correlation between electronic banking services and its axes and achieving the profitability of commercial banks (rate of return on assets) in Jordan from the perspective of employees, and the results indicated the existence of a strong correlation Between electronic banking services and the profitability of commercial banks from the perspective of employees (rate of return on equity) in Jordan. The study recommended several recommendations, including increasing awareness of electronic banking services in Jordanian commercial banks and other banks.